2021
DOI: 10.3390/biomedicines9101339
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell-Mediated Eradication of Ovarian Cancer Cells with a Novel Chimeric Antigen Receptor Directed against CD44

Abstract: Ovarian cancer is the most common cause of gynecological cancer-related death in the developed world. Disease recurrence and chemoresistance are major causes of poor survival rates in ovarian cancer patients. Ovarian cancer stem cells (CSCs) were shown to represent a source of tumor recurrence owing to the high resistance to chemotherapy and enhanced tumorigenicity. Chimeric antigen receptor (CAR)-based adoptive immunotherapy represents a promising strategy to reduce the risk for recurrent disease. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The flow cytometry results for 24-hour incubation of DOX-loaded NGs at levels of DOX below of the typical noticed cytotoxicity (lower that IC50 values; see Figure 11 ) exhibited significantly higher, from 40% to 70%, entry of DOX-loaded NGS to both types of cancer cell lines (MCF-7, A2780) compared to free drug, respectively. It should be noticed that much lower level was noticed for A2780 cell lines that not possess overexpressed typical cellular receptors (CD44, RHAMM) that are characteristic for the interaction of HA (Klapdor et al., 2021 ). The increased level of NGs that entered the MCF-7 suggested that targeted behavior of proposed NGs was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The flow cytometry results for 24-hour incubation of DOX-loaded NGs at levels of DOX below of the typical noticed cytotoxicity (lower that IC50 values; see Figure 11 ) exhibited significantly higher, from 40% to 70%, entry of DOX-loaded NGS to both types of cancer cell lines (MCF-7, A2780) compared to free drug, respectively. It should be noticed that much lower level was noticed for A2780 cell lines that not possess overexpressed typical cellular receptors (CD44, RHAMM) that are characteristic for the interaction of HA (Klapdor et al., 2021 ). The increased level of NGs that entered the MCF-7 suggested that targeted behavior of proposed NGs was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, it was demonstrated that sequential combination therapy with cisplatin followed by CD133-CAR-NK and CD44-CAR-NK92 cells led to the strongest killing effect on ovarian cancer stem cell lines compared to control NK cells [ 252 , 253 ] (Fig. 3 A).…”
Section: Potential Combination Therapies To Enhance Car-cell Functionsmentioning
confidence: 99%
“…For example, prostate stem cell antigen-directed CAR NK cells have shown promising therapeutic efficacy for pancreatic cancer in a preclinical study [11]. Engineered CAR-NK cells targeting CD44, a marker abundantly expressed by ovarian cancer cells, showed potent cytotoxicity against CD44-positive ovarian cancer cells [20]. In lung adenocarcinoma, CAR-NK92 cells targeting mesenchymal-epithelial transition factor (C-Met) showed promising results in lung xenograft models [21].…”
Section: Car-nk Cells Pick Up Where Car-t Cells Left Offmentioning
confidence: 99%